Ժամանակակից տարրական դպրոցի ուսուցիչը և նրա գործունեության տարրերը դպրոցում - Դալլաքյան, Ա․ Հ․
В статье представлена модель современного учителя подходы исследователей и научных деятелей о сущности, структуре, содержании педагогической деятельности. Так- же рассмотрены некоторые концептуальные положения формирования общечеловеческих ценностей учащихся основной школы. Проведен анализ структуры педагогической деятельности, его основных целей. Подчеркнута значимость педагогической деятельности не только в развитии личности, но и в развитии современного общества. The current article presents a model of the modern teacher and the approaches of scientists and researchers about the essence, structure and the content of pedagogical activities. Moreover it covers some conceptual bases of the formation of mankind values for the primary school learners. At the same time analysis of the structure of pedagogical activity and its main objectives was conducted. The role of pedagogical activity is not only underlined in the development of the personality, but also in the modern society.
Keywords: Տարրական կրթություն; Մանկավարժություն